Assessing user engagement with non-digital library resources among undergraduate students at Faculty of Information Science - Shapie, Nurul Nur Fatihah (2025)
Public and academic libraries invest significantly in digital resources yet struggle to justify these expenditures due to low usage. The rise of non-digital library (non-DL) resources challenges the prominence of academic digital libraries. This study examines user engagement with non-DL resources, focusing on reliability, assurance, tangibles, empathy, responsiveness, and satisfaction, framed within the SERVQUAL model. A mixed-methods approach was employed, combining a comprehensive literature review across education, digital libraries, and technology with quantitative data collection. Participants included undergraduate students from the Faculty of Information Science at Universiti Teknologi MARA (UiTM) across multiple campuses. A theoretical model was developed, testing hypotheses related to engagement, service quality, and satisfaction. Analysis of 302 responses confirmed significant relationships between these factors and non-DL engagement. The study contributes theoretically by integrating SERVQUAL with non-DL engagement, empirically validating these relationships, and offering practical tools for assessing non-DL resources. The study's limitations include its focus on a specific student population and potential for broader applicability. Future research should incorporate models like TAM or UTAUT and expand to diverse student groups. Combining qualitative and quantitative methods is recommended for a more comprehensive understanding.